Comparative Analysis of Migration Policy of 18–19th Century Kazakhstan and 20–21st Century Italy - Taskuzhina, Aygul; Khamzina, Leila.; Balzhanova, Aigul; Erisheva, Tolkyn; Isenov, Otegen; Anasova, Ainash; Shakhaman, Zamzagul (International Journal of Euro-Mediterranean Studies, 2017)
The article shows that for over a century Kazakhstan has been a region of active migratory movement. Intensification of some migratory processes in most instances was a consequence of a certain state decision. Italy was chosen as the study object in the Mediterranean region, as the country mostly exposed to illegal migration in terms of acceptance of people for residential stay. Research in migration and integration processes in the EU countries as a political, legal and socio-cultural phenomenon has been of great scientific and practical interest. The article provides a detailed analysis of the legal, historical, and social spheres of the Italian society, and offers to use Kazakhstan‘s experience in resolving the issue of illegal migration.
Keywords: resettlement of the nation; migration trends; use of historical experience; Mediterranean region; historical time perspective; multi-ethnic society